2010
DOI: 10.1002/0471140864.ps0524s61
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Optimize Protein Expression in E. coli

Abstract: Recombinant protein expression in Escherichia coli (E. coli) is simple, fast, inexpensive, and robust, with the expressed protein comprising up to 50 percent of the total cellular protein. However, it also has disadvantages. For example, the rapidity of bacterial protein expression often results in unfolded/misfolded proteins, especially for heterologous proteins that require longer times and/or molecular chaperones to fold correctly. In addition, the highly reductive environment of the bacterial cytosol and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 188 publications
2
123
0
Order By: Relevance
“…Expression of soluble proteins can be regulated through many factors that the host cell normally use in controlling of toxic protein expression [6,8,[12][13][14] .…”
Section: Tight Control Of the E Coli Cellular Milieumentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of soluble proteins can be regulated through many factors that the host cell normally use in controlling of toxic protein expression [6,8,[12][13][14] .…”
Section: Tight Control Of the E Coli Cellular Milieumentioning
confidence: 99%
“…It also has very strong reversible binding attributes allowing for rapid single-step purification. Polyhistidine tags can be attached on either the N-or C-termini of recombinant proteins, but the optimal location depends on the folding and biochemical characteristics of the adjacent recombinant protein [14,20,26,27] .…”
Section: Refolding Of Solubilized and Unfolded Proteinsmentioning
confidence: 99%
“…Failure to achieve native folding in a timely manner can prompt the proteins to aggregate before folding (Esposito andChatterjee 2006, Francis andPage 2010). 116 Various methods have been used to maximise production of soluble recombinant protein in E. coli.…”
Section: Results Inmentioning
confidence: 99%
“…Thus, after bioinformatics evaluations, we designed a truncated fragment of Pta passenger domain (amino acid residues 207-730) which implied a conserved, stable and cell-surface-exposed fragment which was expressed and purified consequently. On the other hand, we showed that the truncated Pta was expressed robustly in pET28a-BL21 [23,24] and could be purified with high quality and concentration (2 mg/ml). By comparing the yield of the purified truncated form of Pta in this study with its full length yield, achieved by Alamuri et al [8] (1 mg/ml), we could find the advantage of truncation of Pta protein in the yield of purification as compared to the full length of Pta.…”
Section: Discussionmentioning
confidence: 98%